DECISION-MAKING MODEL FOR RECEIVING SOCIAL ASSISTANCE FOR COMMUNITIES AFFECTED BY THE COVID-19 PANDEMIC IN BUTI VILLAGE OF MANANGGU DISTRICT OF BOALEMO REGENCY - fitria husuna; darman darman; ghoriqna fibahrilwahdah (LP2M Universitas Bina Mandiri Gorontalo, 2022)
The purpose of the research included finding out the model of decision-making in the provision of social assistance during the Covid-19 pandemic in Buti Village, Mananggu District, Boalemo Regency. This research is a type of descriptive research with a qualitative approach The reason or using a descriptive type of research and qualitative approach is because this research is generated from descriptive data obtained from several writings, words, and documents derived from sources and information that are researched and trusted. The results of the study concluded that the decision-making model of social aid recipients affected by covid 19 through 3 stages, namely 1). The data collection process is carried out the formation of a verifier team to collect candidates who deserve assistance in the field (hamlets), then the verifier team consisting of Dasawisma and the head of the hamlet descends to the hamlets by name by address, as well as reporting the results of the collection of prospective recipients of assistance to the village head as preliminary data. 2). Consolidation and verification of the second stage in the decision-making process of beneficiaries for communities affected by covid 19 is the process of consolidation and verification, in this stage, the village head will sit together with the entire verifier team, BPD, and village companion to discuss thoroughly the results of the initial data collection that has been collected. All the data will be verified until you get the real amount who is most entitled to be recommended to receive assistance, the verification results will be taken to the final validation stage. 3). Validation and Determination of the final stage results in the decision-making process of beneficiaries for communities affected by covid 19 validation and determination of results, in this stage the village head will sit together with the entire verifier team, BPD, and village companions to thoroughly discuss the results of the initial data collection that has been collected. All the data will be validated until the real amount of who is most entitled to be recommended to receive assistance, the validation results will be taken to the stage of determining the results.